Mineral composition of the scallop, Placuna placenta shell from the eastern part of East Java Waters, Indonesia - Indah Wahyuni Abida; Sri Andayani; Uun Yanuhar; H. Hardoko (Caspian Journal of Environmental Sciences)
The shell of bivalve such as Placuna placenta is one of many biomasses that is commonly used as bio-inspired and biomimetic material. Different habitat may influence the living of organism, including the biomineralization of P. placenta shell affecting their mineral composition. This study was aimed to know the mineral composition of the P. placenta shell collected from Ujung Pangkah-Grasik and Junganyar Socah-Bangkalan, Indonesia. Observation was carried out on the shell (near umbo) using SEM-EDX (Scanning Electron Microscope-Energy Dispersive X-ray Spectroscopy). The result showed that the shell collected from Junganyar Socah-Bangkalan have larger element quantities (9 types) than that from Ujung Pangkah-Gresik (6 types). The elements found on the shell collected from Junganyar Socah-Bangkalan were: C, O, Na, Mg, Si, Ca, S, Al, and Cl, while from Ujung Pangkah-Gresik were: C, O, Na, Mg, Ca, Zn, and S. The Na/Ca ratio of the shell from Ujung Pangkah-Gresik was higher than that from Junganyar Socah-Bangkalan. The Mg/Ca and S/Ca ratio of the shell from Junganyar Socah-Bangkalan was higher than that from Ujung Pangkah-Gresik.